Novel calcium encapsulated mesocellular siliceous foams for crystal growth in dentinal tubules. (April 2019) - Wang, Yin-Lin; Chiang, Yu-Chih; Chang, Hao-Hueng; Lin, Hong-Ping; Lin, Chun-Pin
Abstract: Objectives: The aim of this study was to investigate the novel mesocellular siliceous foams (MCF) containing CaCO3 nanoparticles (denoted as CMCF) combined with phosphoric acid could occlude dentinal tubules through the formation of biomimetic crystal barrier. Methods: Ultrastructures of MCF and CMCF were examined by transmission electron microscopy (TEM). Elemental components were analyzed with energy dispersive X-ray spectrometry (EDX). CMCF was mixed with distilled water, 10%, 20% and 30% phosphoric acid then applied on dentine discs. Crystals were characterized by X-ray powder diffractometry (XRD). The sealing efficacy of the dentinal tubules was examined by scanning electron microscopy. Results: TEM images showed MCF presented a pore size of approximately 30.0 nm and CMCF contained abundant nano-CaCO3 . Sealing efficacy showed that CMCF, when reacted with 30% phosphoric acid, would form crystals in the dentinal tubules to a depth of 83.2 ± 17.6 μm at an occlusion percentage of 75.6 ± 12.8% on average; both occlusion percentage and depth were higher than those obtained with 10% or 20% phosphoric acid (p < 0.05). The results of XRD and EDS indicated that the crystal growth in the dentinal tubules could be transformed into the biomimetic crystals. Conclusion: This study showed that the CMCF with 30% phosphoric acid could effectively occlude the dentinal tubules through the formation of biomimetic crystal barrier. Clinical significance: The novel CMCF combined with phosphoric acid may have potential for the treatment of dentine hypersensitivity.